2006
DOI: 10.1021/ic061297q
|View full text |Cite
|
Sign up to set email alerts
|

Tricarboranyl Pentaerythritol-Based Building Block

Abstract: A new tricarborane building block based on pentaerythritol was prepared for applications in boron neutron capture therapy (BNCT). Its X-ray single-crystal structure revealed a high degree of steric congestion. To enable the attachment of the building block to other moieties, a succinimidyl linker has been introduced at the focal point, and a generation-2 hexacarborane-containing dendron carrying 60 boron atoms has been prepared using a 2,2-bis(hydroxymethyl)propionic acid core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Our earlier X-ray crystallographic studies of the tricarboranyl pentaerythritol building block indicated that the ester groups in DC-1 are hindered from the nucleophilic attack by the steric bulk of the tricarboranyl pentaerythritol wedge. 66 Similar results, indicating stability of DC-1 , were obtained in DMEM and RPMI-1640 cell culture media.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Our earlier X-ray crystallographic studies of the tricarboranyl pentaerythritol building block indicated that the ester groups in DC-1 are hindered from the nucleophilic attack by the steric bulk of the tricarboranyl pentaerythritol wedge. 66 Similar results, indicating stability of DC-1 , were obtained in DMEM and RPMI-1640 cell culture media.…”
Section: Resultssupporting
confidence: 70%
“… 53 − 55 To date, there have been several reports of multiple polyhedral boranes conjugated to macromolecular scaffolds such as dendrimers, 56 65 making this type of chemistry particularly attractive for our purpose. We chose tri- o -carboranyl pentaerythritol, whose synthesis we previously reported, 66 as the building block of our dendritic wedge.…”
Section: Resultsmentioning
confidence: 99%
“…Tripropargyl ether 4 was prepared in three steps from pentaerythritol according to the procedure described by Zharov 20. The resulting primary alcohol (i.e., 4 ) then reacted with 2‐chloroethyl ether to give 5 ,19 the starting material for the first CuAAC reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The same process was repeated for the synthesis of trivalent iminosugars 13 (Scheme ). The tripropargyl ether 11 ,30 prepared in three steps from pentaerythritol, was treated with azide precursors 8 and subsequently deprotected to provide the desired trivalent iminosugars in almost quantitative yields for the two steps. To complete the series, hepta‐ and 14‐valent cyclodextrin‐based iminosugar clusters 2 and 3 were efficiently synthesized by a CuAAC reaction, according to our previously reported strategy,23 as well as monovalent controls 5 that were used to assess the multivalent effect (Scheme ).…”
Section: Resultsmentioning
confidence: 99%